En-gendering individuals : the language of re-forming in twentieth century Keralam - Devika, J. (New Delhi : Orient Longman, 2007)
Articles with reference to early 20th century Kerala, India.
Includes bibliographical references and index.
Keywords: Feminism -- India -- Kerala -- History -- 20th century; Social change -- India -- Kerala -- History -- 20th century; Women in literature; Society in literature